Investigating the Effect of Heterogeneous Hull Roughness on Ship Resistance Using CFD - Soonseok Song; Yigit Kemal Demirel; Claire De Marco Muscat-Fenech; Tonio Sant; Diego Villa; Tahsin Tezdogan; Atilla Incecik (Journal of Marine Science and Engineering, 2021)
Research into the effects of hull roughness on ship resistance and propulsion is well established, however, the effect of heterogeneous hull roughness is not yet fully understood. In this study, Computational Fluid Dynamics (CFD) simulations were conducted to investigate the effect of heterogeneous hull roughness on ship resistance. The Wigley hull was modelled with various hull conditions, including homogeneous and heterogeneous hull conditions. The results were compared against existing experimental data and showed a good agreement, suggesting that the CFD approach is valid for predicting the effect of heterogeneous hull roughness on ship resistance. Furthermore, the local distributions of the wall shear stress and roughness Reynolds number on the hull surface were examined to assess the flow characteristics over the heterogeneous hull roughness.